ANALISIS KINERJA DAN SISTEM PEMELIHARAAN GENERATOR SET (GENSET) PADA APARTEMENT GREEN CENTRAL CITY - Sumanto; Insani Abdi Bangsa (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
ABSTRACT The existence of a generator in the apartment is very very important. If the main electricity supply from PLN is off or under repair, the generator will work as a power supply for backup electricity. The size of the generator has an important role in generating electricity. The generator component consists of a power generator with a series of propulsion engines that work together to produce a certain amount of electricity using fuel. The place where this research was carried out was at the Green Central City Apartment. The generator used by the Green Central City Apartment is a generator with the MAN brand with type D2842 – LE213 as many as 3 units. The capacity of the generator used at Green Central City Apartments is 800 kVA and 700 kVA. The generator maintenance process at the Green Central City Apartment is carried out regularly. The process of checking the generator is carried out by checking several important components such as the condition of the battery, fuel supply, radiator water, and engine oil. In addition, the generator engine will be turned on as a step to heat the engine and also record data on the generator which can be seen on the control panel. Further maintenance is carried out based on the operating hours of the generator. For the treatment process, follow the procedure. Keywords: Generator; Apartement; Maintenance ABSTRAK Keberadaan Genset di Apartement sangat amat penting. Jika pasokan listrik utama dari PLN sedang mati atau dalam perbaikan makan Genset akan bekerja sebagai Power Supply untuk cadangan listrik. Ukuran genset memiliki peran penting dalam menghasilkan besaran listrik. Komponen Genset terdiri atas pembangkit tenaga dengan rangkaian mesin penggerak yang bekerja sama untuk menghasilkan listrik daya tertentu menggunakan bahan bakar. Tempat pelaksaan dari penelitian ini dilakukan pada Apartemen Green Central City.Genset yang digunakan oleh Apartemen Green Central City yaitu Genset Dengan Merek MAN dengan tipe D2842 – LE213 sebanyak 3 unit. Kapasitas genset yang digunakan pada Apartemen Green Central City adalah 800 kVA dan 700 kVA. Untuk proses pemeliharaan genset di Apartemen Green Central City ini dilakukan secara berkala. Proses pengecekan genset dilakukan dengan pengecekan beberapa komponen penting seperti kondisi baterai, persediaan bahan bakar, air radiator, serta oli mesin. Selain itu juga mesin genset akan dinyalakan sebagai langkah untuk memanaskan mesin dan juga mencatat data – data pada genset yang dapat dilihat pada panel kontol. Untuk perawatan selanjutnya dilakukan berdasarkan jam operasional dari genset. Untuk proses perawatannya mengikuti prosedur. Kata Kunci: Genset; Apartemen; Pemeliharaan